Risk factors for ischemic stroke in the elderly in Morocco – a case-control study - Arzoug, Hafid; Loubna, Chouaf; Amine, Baba Med; Lahoucine, Amsdar; Adali, Nawal (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Ischemic strokes occur most frequently in the elderly (more than 80%). This study aimed to determine the risk factors for ischemic stroke in elderly subjects in the Souss Massa region of southern Morocco. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. Two hundred and thirteen cases and four hundred and thirty-two controls of the same age (76.51±2 years vs. 73.90±2 years) and sex were collected. Cases were selected from patients with ischemic stroke hospitalized in the neurology department of the regional hospital Souss Massa. All risk factors have been documented from interviews and review of patient medical records. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. Multivariate regression analysis showed that low-income families (odds ratios [OR]=4.19, 95% confidence intervals [95% CI] 2.886–6.09, p<0.001), residence area (urban OR=9.408, 95% CI 4.7133–18.778, p<0.001), high blood pressure (OR=62.984, 95% CI 26.7374–148.367, p<0.001), diabetes (OR=18.138, 95% CI 5.2320–62.880, p<0.001), are risk factors for ischemic stroke. On the contrary, health insurance (OR=0.295, 95% CI 0.1513–0.577, p<0.001) and marital status (in couple OR=0.448, 95% CI 0.284–0.708, p<0.001) are protective factors. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. In addition to traditional risk factors of ischemic strokes such as high blood pressure and diabetes, low-income family as well as lack of health insurance and marital status (living with a partner) require particular attention. Integrating these new factors into public health strategies could significantly reduce the risk of stroke in the elderly.